AN ATTEMPT TOWARDS LABORATORY AND CLINICAL COMBINE APPRAISED, INCLUDING FUTURE CONCERNS REGARDING DENGUE INFECTION - Ali, Qaisar; Kalam, Irfan; Mabood, Fazal; Imran, Muhammad (Journal of Ayub Medical College Abbottabad, 2020)
Background: Dengue infection is a deadly global pandemic due to its fatal nature, being emerged from mild stage to turn into more severe stages and consequently causing casualties. it upsurges various phases, namely subclinical infection, undifferentiated febrile fever, Dengue fever (DF) and devastating states which often ends to life, they are Dengue haemorrhagic fever (DHF) and Dengue shock syndrome (DSS). Dengue infection is a mosquito born disease which has engulfed many regions in general and tropical zone in particular, causing many casualties and has posed a threat to humanity, demanding strategies to resolve the global issue. It is reported that 50-200 million people fall prey to it globally by dint of its causative agents and imperative to mention that over proportional are the minor among the victims. Because of awful joint pain dengue fever is also named break bone fever. The common indicator in infected individuals is thrombocytopenia, coagulopathy and vasculopathy. Apart from supportive therapy, no aphoristic therapy has been introduced so far, however care may prove rescuer. Timely prognosis thwarts to enter it in deteriorating phase. In the list of laboratory diagnosis virus serology and detection of Ribonucleic acid are primed. In general, there's no specific decisive diagnostic biomarker present through which accurate and prompt prognosis can possible during the entire patient presentation time, particularly in case of secondary dengue infection. Although, through the advancement and commercialization of point-care combined tests, capable of tracking disease markers present during various phases of infection (viral non-structural protein 1 and immunoglobulin M), such evaluation massively improved the treatment through lab-based. Despite such improvements, major hurdles persist in the clinical management of patients with dengue infection, particularly lack of dependable biomarkers that have an efficacious prognostic gauge to predict steady progress to severe disease. In the described review both clinical and laboratory diagnosis of dengue infection have been highlighted, including concern regarding future accessibility. Keywords: Dengue shock syndrome; Dengue haemorrhagic fever; thrombocytopenia; Dengue fever